Comparison of four matrixes for diluting insulin in routine clinical measurements. Issue 9 (7th June 2020) - Li, Honglei; Wang, Danchen; Guo, Xiuzhi; Xia, Liangyu; Wu, Qiong; Cheng, Xinqi
Abstract: Objective: In our laboratory, 2.36% (6626/280765) samples obtained for insulin evaluation have serum insulin concentrations higher than 300 mU/L, resulting in curves outside the linear range in the insulin release test (IRT). Accordingly, using appropriate dilution protocols to determine insulin concentration accurately is important. Here, we compared the effectiveness and economy of four different solutions for diluting high‐insulin serum in routine clinical measurements. Method: Residual serum samples with high‐insulin concentrations ranging from 200 to 300 mU/L were collected in Peking Union Medical College Hospital from August to November 2017. Four different matrixes including a Siemens original diluent, pure water, 0.9% NaCl, and low‐insulin serum (labeled as A to D, respectively) were used to dilute the serum in the ratios of 1:2, 1:5, and 1:10. Results: We found that the linear correlation coefficients of A to D were higher than 0.9. The recovery rates of A to D were 86.4%–104.0%, 73.2%–99.3%, 76.4%–101.3%, and 84.2%–99.7%, respectively. We conclude that the use of 0.9% NaCl, pure water, or low‐insulin serum to dilute high‐serum insulin (>300 mU/L) is feasible and cost‐effective. Conclusion: We recommend a dilution factor of 1:5 on a Siemens ADVIA Centaur XP ® instrument. The clinically reported range was 0.5‐1500 mU/L. For specific samples (>1500 mU/L), we recommended using low‐insulin serum samples for dilution.